2009
DOI: 10.14236/jhi.v17i2.721
|View full text |Cite
|
Sign up to set email alerts
|

Clinical informatics to improve quality of care: a population-based system for patients with diabetes mellitus

Abstract: Background The prevalence of diabetes mellitus is increasing in the USA. However, control of intermediate outcome measures remains substandard. Recently, significant emphasis has been placed on the value of electronic medical records and informatics systems to improve the delivery of health care. Objective To determine whether a clinical informatics system improves care of patients with diabetes mellitus. Methods In this quality improvement pilot initiative, we identified 48 patients with diabetes mellitus who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Specifically, one might continue to emphasize alerts in the medical record or nurse management to improve care. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, one might continue to emphasize alerts in the medical record or nurse management to improve care. 33 …”
Section: Discussionmentioning
confidence: 99%
“…16 A variety of strategies have been used including the use of diabetic patient registers, tracking HbA1c tests, point of care decision support tools and clinician reminders. [17][18][19] These strategies have mainly been evaluated in a quality improvement framework and in some cases required the augmentation of existing electronic medical record systems. 17 While it is acknowledged that data extraction tools can be very useful for identifying, quantifying and monitoring clinical practice issues, considerable technical barriers have been identified that potentially limit their usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…34 Impact on processes of care and clinical outcomes Diabetes registers and EMRs used for tracking diabetes patients are implicitly and explicitly promoted as effective and necessary management tools with the potential for improving diabetes care. 35,36 The extent to which this information system is developed, updated and integrated by health professionals into the process of care for diabetes patients depends on whether they believe that a diabetes register will impact on patient quality of care and outcomes. 11,15 Modern healthcare systems support the increased use of diabetes registration systems in order to improve the management of patient records and the quality and cost-effectiveness of patient care.…”
Section: Discussionmentioning
confidence: 99%